Properties of CdTe thin films prepared by hot wall epitaxy - Bilevych, Ye.O.; Boka, A.I.; Darchuk, L.O.; Gumenjuk-Sichevska, J.V.; Sizov, F.F.; Boelling, O.; Sulkio-Cleff, B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
CdTe thin films were grown on different substrates: BaF₂ (111), polished Si (100), SiO₂, bulk CdTe (110) and HgxCd₁₋xTe layers by hot wall epitaxy (HWE). Chosen temperature parame-ters and technological process of thin film fabrication provided the growth rate of about 0.03 mm/min. The current-voltage characteristics and transmission spectra were measured. X-ray diffrac-tion data (XRD) measurements were carried out as well.